Enhancing Healthcare Quality through Integrated Pharmacy, Medical Device Maintenance, Nursing, and Health Management Practices in Infection Control in Saudi Hospitals - Mohammed Omar Almehmadi; Sama Abd Alrazq Othman; Hassan Ali Alfaqeeh; Ahmed Hamoud Alharthi; Mubarak Abed Mubarak Alsuwat; Safwan Habib Alsaedi; Mohammed Mubarak Alzahrani; Yousef Khamis Alshammari; Yassir Abdullah Baqadir; Ahmed Hassan Ahmed Alshehri; Sattam Musleh Alrashede; Faiz Faisal Fahad Alshammari (International Journal of Medical Toxicology and Legal Medicine, 2024)
Infection control is one of the cornerstones and a critical aspect of patient safety in the delivery of healthcare, especially in hospitals, due to the risks associated with healthcare-associated infections. HAIs increase not only the morbidity and mortality rates of patients but also the length of stay in the hospital, hence leading to higher treatment costs. The need is to address such challenges in an affirmative manner, especially in Saudi Arabia, which is doing all it can to ensure that hospitals improve to meet international standards of health care. Pharmacy services, maintenance of medical devices, nursing practices, and health management all go hand in glove in taking infection control strategies forward and making the healthcare environments safer for the overall purpose of improvement in patient care outcomes. Pharmacy services represent an important part of infection control through programs on antimicrobial stewardship which would optimize antibiotic use and limit the emergence of antimicrobial resistance. Pharmacists also have a crucial role in assuring appropriate medication handling, storage, and preparation to minimize the risks of contamination. Their role in educating healthcare teams about antimicrobial use and infection prevention underlines their importance in multidisciplinary infection control efforts. Another critical pillar of infection control is maintaining medical devices. Poorly sterilized or malfunctioning devices can serve as major vectors for HAIs. Regular check-up, cleaning, and maintenance in accordance with the international standard on device management should be ensured to evade infection hazards. The maintenance teams must coordinate their effort with health care providers so that all equipment is safe and operational, which justifies the establishment of operational strategies within a hospital. Nursing practices are considered the front line of defense against infection prevention and control. Nurses follow hygiene practices themselves and monitor infection control policies; they can include teaching prevention to their patients and their families as well. It is because of this close contact with the patient that they are often in an unparalleled opportunity to contribute greatly toward the objective of reduction in HAIs. Lastly, health management ensures that infection control will be given support through hospital policies, proper training, and resources. It also requires multi-disciplinary collaboration and evidence-based practices as cornerstones in the operationalization of infection control for Saudi hospitals to achieve full patient safety and health care quality.